Association between white blood cell counts and the efficacy on cognitive function after rTMS intervention in schizophrenia - Suzhen Ye; Bailing Wang; Heling Sui; Meihong Xiu; Fengchun Wu (Schizophrenia)
Abstract rTMS has shown some effect in improving cognitive functions in patients with schizophrenia. However, these findings were controversial, and specific mechanisms of action and optimal therapeutic parameters still require further investigation. This study aimed to examine predictive biomarkers of the efficacy of rTMS in cognitive improvement in schizophrenia. A secondary analysis of a previous randomized, controlled trial was performed. Fifty-six patients were allocated to the active rTMS and 28 to the sham group. Patients received 6 weeks of treatment and were followed up for 18 weeks. Cognition was assessed and blood biomarkers were measured in all patients. In patients with schizophrenia, there was a significant interaction between time and group on immediate memory. Furthermore, this study found that after controlling for confounders, patients with higher baseline white blood cell (WBC) counts showed less improvement in immediate memory after rTMS than patients with lower WBC counts. Linear regression analysis showed that WBC counts were associated with immediate memory improvement after rTMS treatment. Our results reveal that WBC counts at baseline correlated with the response to rTMS in patients with schizophrenia. Patients with higher baseline WBC counts improved less after rTMS intervention than those with lower WBC counts.